Perancangan Sistem Informasi Pelabuhan Labuhan Haji Berbasis Website (Journal Digital Technology Trend, 2022)
Keeping up with technological developments applied to transportation facilities, it is very rare to find sea transportation facilities that can be accessed on a web-based basis, both from departure schedules, information and for booking tickets with one company. This research attempts to design an Android-based mobile application that can solve the problem of ticket ordering and ship departure schedules at the Sinabang Haj port crossing. This application will take advantage of the fast access that the web has that is used to order boat tickets, find out the departure schedules of various ships that will sail around Lintas Labuhan Haji Sinabang. The development method used is the linear sequential model, which is often called the Waterfall Model, which is the most widely used software engineering paradigm. From the research results, it can be concluded that; from the results of making web-based ticket reservations by PT. ASDP Indonesia Ferry (Persero) Labuhan Haji makes it easy to inform ticket reservations and schedules that are ready through the booking system. With the website, the public can access and obtain information and order website-based tickets quickly from their homes, and can choose the desired departure schedule, and The ticket rental application on the Website-based Labuhan Haji Sinabang Information System Design can handle and control and monitor ticket, schedule, ship data, which can avoid delays and in making reports for each transaction activity.